Spatial Variability of Radon Production Rates in an Alluvial Aquifer Affects Travel Time Estimates of Groundwater Originating From a Losing Stream. Issue 4 (1st April 2022) - Schaper, Jonas L.; Zarfl, Christiane; Meinikmann, Karin; Banks, Eddie W.; Baron, Sandra; Cirpka, Olaf A.; Lewandowski, Joerg
Abstract: Assessing water travel times in hyporheic and adjacent alluvial sediments is important to quantify exchange rates, biogeochemical turnover, and pollution dynamics across groundwater‐surface water interfaces and in floodplain aquifers. Heat and 222 Rn are useful natural tracers for this purpose. While heat transport is commonly simulated via the convection‐conduction equation, the transport of 222 Rn is often simulated assuming purely advective transport and a homogenous distribution of 222 Rn production rates across the model domain. In the present study, we explicitly model the production, transport, and radioactive decay of 222 Rn after surface water infiltration into an alluvial aquifer with the numerical models MODFLOW‐NWT and MT3D‐USGS. Using field observations, numerical modeling, and laboratory experiments, we show that 222 Rn production rates vary substantially in the alluvial aquifer of a lowland river. Distributions of mean river‐to‐groundwater travel time in the alluvial aquifer, estimated via a Bayesian approach, shifted considerably depending on whether 222 Rn and time series of groundwater heads and temperature were jointly inverted and whether 222 Rn production rates were allowed to vary spatially. With distance to the river, differences between the median river‐to‐groundwater travel time and apparent 222 Rn ages increased by factors ranging from 1.4 at 4 m to 11.9 at 59 m, a finding that highlights the need to simulate 222 Rn transport explicitly. The joint inversion of 222 Rn, groundwater heads, and temperature reduced uncertainty associated with mean travel times, suggesting that the uncertainty introduced by spatially varying 222 Rn production rates can at least partly be compensated by using a combination of natural tracers. Plain Language Summary: Rivers and groundwater bodies exchange water back and forth. Knowing the time that water spends traveling from rivers to certain points in groundwater is important for water management, particularly in situations where drinking water is produced via bank filtration: It allows to predict what happens to natural and toxic compounds that come from the river and to assess the quantity of water moving from rivers to aquifers. Here, we present a modeling approach to estimate travel times of groundwater originating from a nearby river. The approach uses the open‐source software packages MODFLOW‐NWT and MT3D‐USGS and a combination of natural tracers, such as the noble gas 222 Rn, which is produced in the subsurface with varying rates but decays with a constant rate constant. We demonstrate that by using both 222 Rn and other natural tracers, such as heat, we estimate travel times from rivers to points in groundwater with less uncertainty. Key Points: A flexible approach to explicitly model the transport of 222 Rn in saturated porous media using MODFLOW‐NWT and MT3D‐USGS is presented Spatially varying 222 Rn production rates, found to vary by a factor of two at relatively small spatial scales (<100 m), are considered A joint inversion of hydraulic heads, temperature, and 222 Rn reduced the high degree of uncertainty in the estimated groundwater travel times